Group IV phospholipase A(2)alpha controls the formation of inter-cisternal continuities involved in intra-Golgi transport. - Enrica San Pietro (Public Library of Science (PLoS), 2009)
The organization of intra-Golgi trafficking and the nature of the transport intermediates involved (e.g., vesicles, tubules, or tubular continuities) remain incompletely understood. It was recently shown that successive cisternae in the Golgi stack are interconnected by membrane tubules that form during the arrival of transport carriers from the endoplasmic reticulum. Here, we examine the mechanisms of generation and the function of these tubules. In principle, tubule formation might depend on several protein- and/or lipid-based mechanisms. Among the latter, we have studied the phospholipase A(2) (PLA(2))-mediated generation of wedge-shaped lysolipids, with the resulting local positive membrane curvature. We show that the arrival of cargo at the Golgi complex induces the recruitment of Group IVA Ca(2+)-dependent, cytosolic PLA(2) (cPLA(2)alpha) onto the Golgi complex itself, and that this cPLA(2)alpha is required for the formation of the traffic-dependent intercisternal tubules and for intra-Golgi transport. In contrast, silencing of cPLA(2)alpha has no inhibitory effects on peri-Golgi vesicles. These findings identify cPLA(2)alpha as the first component of the machinery that is responsible for the formation of intercisternal tubular continuities and support a role for these continuities in transport through the Golgi complex.